MANF attenuates neuronal apoptosis and promotes behavioral recovery via Akt/MDM‐2/p53 pathway after traumatic spinal cord injury in rats. (24th May 2018) - Gao, Liansheng; Xu, Weilin; Fan, Shuangbo; Li, Tao; Zhao, Tengfei; Ying, Guangyu; Zheng, Jingwei; Li, Jianru; Zhang, Zhongyuan; Yan, Feng; Zhu, Yongjian; Chen, Gao
Abstract: The aim of this study was to investigate the potential effect and mechanism of action of MANF in attenuating neuronal apoptosis following t‐SCI. A clip compressive model was used to induce a crush injury of the spinal cord in a total of 230 rats. The Basso, Beattie, and Bresnahan (BBB) score, spinal cord water content, and blood spinal cord barrier (BSCB) permeability were evaluated. The expression levels of MANF and its downstream proteins were examined by western blotting. Immunofluorescence staining of MANF, NeuN, GFAP, Iba‐1, cleaved caspase‐3, and TUNEL staining were also performed. Cells were counted in six randomly selected fields in the gray matter regions of the sections from two spinal cord sites (2 mm rostral and caudal to the epicenter of the injury) per sample. A cell‐based mechanical injury model was also conducted using SH‐SY5Y cells. Cell apoptosis and viability were assessed by flow cytometry, an MTT assay, and trypan blue staining. Subcellular structures were observed by transmission electron microscopy. MANF was mainly expressed in neurons. The expression levels of MANF, and its downstream target, p‐Akt, were gradually increased and after t‐SCI. Treatment with MANF increased Bcl‐2 and decreased Bax and CC‐3 levels; these effects were reversed on treatment with MK2206. The BBB score, spinal cord water content, and BSCB destruction were also ameliorated by MANF treatment. MANF decreases neuronal apoptosis and improves neurological function through Akt/MDM‐2/p53 pathway after t‐SCI. Therefore, MANF might be a potential treatment for patients with t‐SCI. © 2018 BioFactors, 44(4):369–386, 2018